A Grammatical Reference Analysis of Bobby Mook's "FOMO" TED Talk - Pane, Yuneth Johanna; Latumahina, Gian Jelastha; Madiuw, Jenifer Helena (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study examines the strategic use of grammatical reference devices, including personal, demonstrative, and comparative references, in Bobby Mook's "FOMO" TED Talk. The analysis aims to elucidate how these linguistic mechanisms contribute to the overall communicative impact and persuasiveness of influential public discourse. Employing a qualitative methodology, the researcher systematically identifies and analyzes the referential patterns present in the talk's transcript. The findings reveal that Mook leveraged personal pronouns to foster audience engagement and a sense of shared experience, demonstrative references to direct attention to key narrative elements, and comparative references to highlight the nuances of the fear of missing out phenomenon. The synergistic interplay of these referential devices enabled Mook to craft a compelling, coherent, and emotionally resonant presentation that resonated with the TED Talk audience. The discussion situates these findings within the broader context of contemporary research on grammatical cohesion and its role in influential public discourse. Suggestions for future research include expanding the analytical framework to a wider corpus of TED Talks, integrating multimodal analysis, and exploring the application of the methodology to other genres of impactful spoken and written communication.